2021
DOI: 10.1038/s41598-021-93974-3
|View full text |Cite
|
Sign up to set email alerts
|

Salt-tolerance screening in Limonium sinuatum varieties with different flower colors

Abstract: Limonium sinuatum, a member of Plumbaginaceae commonly known as sea lavender, is widely used as dried flower. Five L. sinuatum varieties with different flower colors (White, Blue, Pink, Yellow, and Purple) are found in saline regions and are widely cultivated in gardens. In the current study, we evaluated the salt tolerance of these varieties under 250 mmol/L NaCl (salt-tolerance threshold) treatment to identify the optimal variety suitable for planting in saline lands. After the measurement of the fresh weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…These results indicated that high salt stress inhibited the growth of S. portulacastrum and significantly reduced their biomass. These findings are consistent with the results from previous studies [56,57]. Plants face difficulties in absorbing water and may even experience dehydration when subjected to NaCl treatment due to the decreased water potential of the surrounding solution.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicated that high salt stress inhibited the growth of S. portulacastrum and significantly reduced their biomass. These findings are consistent with the results from previous studies [56,57]. Plants face difficulties in absorbing water and may even experience dehydration when subjected to NaCl treatment due to the decreased water potential of the surrounding solution.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies indicated that MDA could act as the main osmotic regulator and important maker of oxidant stress in plants under salt stress. Moreover, the increase in proline content could also be beneficial to improve the water retention capacity of cells under salt stress ( Xu et al., 2021 ; Zhang et al., 2022 ). When tomatoes were subjected to salt stress, large amounts of reactive oxygen species (ROS) was induced to generate ( Apel and Hirt, 2004 ; Waszczak et al., 2018 ), and the activity of SOD, POD, CAT and other ROS scavengers was accordingly increased to remove the excess ROS to maintain the redox equilibrium in the plant ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies of salinity tolerance have been performed recently involving a number of halophyte species from the same or similar habitats [ 14 , 15 ]. However, studies comparing different accessions or genotypes of a single halophyte species have been seldomly performed [ 16 , 17 , 18 ]. Recently, we performed a study involving a number of accessions of crop wild relative legume species Trifolium fragiferum and concluded that high intraspecies variability in morphological and physiological responses to salinity exist between geographically isolated populations [ 19 ].…”
Section: Introductionmentioning
confidence: 99%